Effects of physical activity on visual outcomes among type 2 diabetes patients: protocol for a scoping review of randomized controlled trials - Ebenezer Oduro Antiri; Thomas Hormenu; Stephen Ocansey; Edward Wilson Ansah (Systematic Reviews)
Abstract Background Type 2 diabetes mellitus remains a major global health concern, affecting millions of patients worldwide resulting in complications, including diabetic retinopathy, one of the leading causes of blindness. Despite the existence and popularity of lifestyle interventions like physical activity in managing diabetes, there is limited evidence exploring higher evidence like randomized controlled trials (RCTs) that have investigated these interventions and their relation with visual outcomes in people with type 2 diabetes mellitus. This protocol outlines a scoping review method that aims to explore literature that used RCTs to study the effects of physical activity interventions on visual outcomes in persons with T2DM. Methods This scoping review protocol will be guided by the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) and the JBI framework for conducting scoping reviews. Thorough search strategies will be designed across databases, including MEDLINE, Cochrane CENTRAL, and JSTOR. Searches will be conducted in clinical registries to supplement the search in the above databases. The studies will be included in this review if they are RCTs conducted among individuals with T2DM and measured the effects of physical activity on visual outcomes. Because this is a scoping review, all relevant studies will be included without a risk-of-bias assessment. The data will be extracted, charted, and analyzed to give an overview of the interrelations of the variables in the literature. The review is expected to be completed by end of June 2025. Discussion Despite the debilitating effects of diabetes, including its telling effects on the eye and vision, the thoroughness of the evidence concerning physical activity clinical trials, and how they affect visual outcomes in people with T2DM, is yet to be assessed. While acknowledging potential limitations like language limits and publication bias, this review seeks to provide valuable insight regarding the contribution of physical activity in enhancing visual health among T2DM patients. This review aims to synthesize evidence from RCTs to contribute to broader discussions on clinical care and policy-making and to encourage future research efforts. Systematic review registration The scoping review protocol has been registered on the Open Science Framework ( https://osf.io/856yb ).